(untitled) (Huellas, 2022)
Urban spaces in Latin America and the Caribbean have become strategic centers of experimentation of city models that allow the reproduction of capital. This paper reflects on the link between neoliberal urbanism and urban restructuring, focusing on the role played by the Inter-American Development Bank (IDB) in the planning of intermediate cities in the region. For this purpose, we take as case studies the programs "Emerging and Sustainable Cities Initiative" (ICES) and "Development of Metropolitan Areas of the Interior" (DAMI), both implemented in the last decade (2011-2021) in the Metropolitan Area of Mendoza (AMM), Argentina. We analyze the central role played by the UNICIPIO-IDB alliance in metropolitan management, focusing on the axes of citizen security and urban transformation interventions in central areas. The work carried out shows the key role played by the IDB, in alliance with UNICIPIO, through its technical advice and the financing of certain urban programs, progressively determining the urban agenda and implementing neoliberal urban models, under the discourse of sustainability. A qualitative methodological design was carried out, focused on case analysis. We used secondary sources, mainly those official documents prepared by the IDB, the provincial government, UNICIPIO and the Municipality of Mendoza, as well as journalistic articles and sectorial magazines.